Impact of cytokine release syndrome on cardiac function following CD19 CAR-T cell therapy in children and young adults with hematological malignancies. Issue 2 (3rd September 2020) - Shalabi, Haneen; Sachdev, Vandana; Kulshreshtha, Amita; Cohen, Julia W; Yates, Bonnie; Rosing, Doug R; Sidenko, Stanislav; Delbrook, Cindy; Mackall, Crystal; Wiley, Brandon; Lee, Daniel W; Shah, Nirali N
Abstract : Background: Chimeric antigen receptor (CAR) T-cell-associated cytokine release syndrome (CRS) may present with tachycardia, hemodynamic instability and reduced cardiac function. Pediatric CAR studies examining cardiac toxicity are limited. Methods: We report on cardiac toxicity observed in children and young adults with hematologic malignancies enrolled in a CD19-28ζ CAR T-cell phase I trial (NCT01593696 ). All patients had a formal baseline echocardiogram. Real-time studies included echocardiograms on intensive care unit (ICU) transfer, and serial troponin and pro-B-type natriuretic peptide (pro-BNP) in the select patients. Results: From July 2012 to March 2016, 52 patients, with a median age of 13.4 years (range 4.2–30.3) were treated. CRS developed in 37/52 (71%), which was grade 3–4 CRS in nine patients (17%). The median prior anthracycline exposure was 205 mg/m 2 (range 70–620 mg/m 2 ) in doxorubicin equivalents. The median baseline left ventricle ejection fraction (LVEF) and baseline LV global longitudinal strain (GLS) were 60% (range 50%–70%) and 16.8% (range 14.1%–23.5%, n=37) respectively. The majority, 78% (29/37), of patients had a reduced GLS <19% at baseline, and 6% (3/52) of patients had baseline LVEF <53%. ICU transfers occurred in 21 patients, with nine requiring vasoactive hemodynamic support and three necessitating >1 vasopressor. Six (12%) patients developed cardiac dysfunction (defined by >10% absolute decrease in LVEF or new-onset grade 2 or higher LV dysfunction, per CTCAE v4), among whom 4 had grade 3–4 CRS. Troponin elevations were seen in 4 of 13 patients, all of whom had low LVEF. Pro-BNP was elevated from baseline in 6/7 patients at the onset of CRS, with higher levels correlating with more severe CRS. Cardiac dysfunction fully resolved in all but two patients by day 28 post-CAR. Conclusion: Cardiac toxicity related to CD19-28ζ CAR T-cell-associated CRS was generally reversible by day 28 postinfusion. Implementation of more frequent monitoring with formal echocardiograms incorporating systemic analysis of changes in GLS, and cardiac biomarkers (troponin and proBNP) may help to earlier identify those patients at highest risk of severe cardiac systolic dysfunction, facilitating earlier interventions for CRS to potentially mitigate acute cardiac toxicity.